Wudu as a form of Islamic water therapy: Insights from hadith and ecotherapy studies - Dzulfaidhi Hakimie Dzulraidi; Mohd Solleh Ab Razak; Umar Muhammad Noor; Mohd Dahlan A. Malek (RSIS International, 2025)
The approach of ecotherapy in health has been gaining increasing attention in modern medicine, particularly in enhancing mental well-being through interaction with natural elements. In Islam, this concept can be linked to acts of worship that involve the use of natural elements, such as wudu (ablution). Wudu is not only a physical purification ritual before prayer but also holds significant spiritual and psychological dimensions. This study aims to assess wudu as a form of ecotherapy in Islam by analyzing relevant hadiths from the perspective of fiqh al-hadith. The study employs content analysis methodology, examining hadith texts from major hadith compilations alongside scholars’ interpretations regarding the effects of wudu on spiritual and emotional well-being. Thematic analysis is used to identify therapeutic elements within wudu, including the role of water as a cleansing and calming element, as well as how wudu contributes to stress and anger management based on the guidance of Prophet Muhammad (SAW). The findings indicate that wudu exhibits characteristics of ecotherapy, particularly in the use of water as a therapeutic instrument, spiritual tranquility, and mental well-being restoration. This study suggests that wudu is not merely a ritual act of worship but also a holistic Islamic therapy that can be applied in the context of mental health treatment among Muslims. Further research is recommended to explore in greater depth the relationship between wudu and psychological well-being through empirical approaches, such as field studies or experiments examining the psychological effects of wudu in stressful and anxiety-inducing situations.